THE COMPARATIVE RESEARCH ON CONJUNCTIONS OF COMPARISON OF ENGLISH AND UZBEK LANGUAGES - Saidvaliyeva, Fotima (QO‘QON UNIVERSITETI XABARNOMASI, 2025)
English and Uzbek are two distinct languages that use different conjunctions to join words and clauses together. In English, conjunctions are used to join words and clauses together in order to create compound sentences. Common English conjunctions include “and,” “but,” “or,” “so,” “if,” “because,” and “although.” In Uzbek, conjunctions are used to link words, phrases, and clauses together to create compound sentences. Common Uzbek conjunctions include “agar,” “ki,” “ammo,” “ya’ni,” “shunda,” “balo,” and “garchi.” One major difference between English and Uzbek is the difference in conjunctive frequency. In English, the conjunctions “and” and “but” are the two most commonly used conjunctions, often appearing in nearly every sentence. In Uzbek, the conjunctions “agar” and “ki” are the two most frequently used conjunctions, appearing often in spoken and written Uzbek. Another notable difference between English and Uzbek is the way in which the two languages use conjunctions for emphasis. In English, the conjunction “but” is often used to draw attention to a contrast between two clauses or phrases. In Uzbek, the conjunction “ammo” is most commonly used for emphasis. In this article variety of conjunctions will be observed, compared and analyzed below.